The effectiveness of palm oil clinker (POC) in gabion wall for slope protection - Lim, Li Yang (2019)
Palm oil clinker (POC) is a waste by-product of palm oil industry that usually treated as waste which may cause problem to the environment sustainability. Gravel is the main material of gabion wall. However, gravel is non-renewable resources on earth, so alternative material has to be suggested to reduce the usage of gravel. This research studied about the effectiveness of palm oil clinker to use as raw material of gabion wall for slope protection. The primary objective of this study is to study the effectiveness of POC in replacing the gravel in gabion wall with 0%, 20%, 50%, 80%, and 100% in term of volume. Gabion wall was used to sustain the slope model consisting of soil sample with critical angle of 60°. Constant rain intensity was added on the slope and transducer reading that recorded the movement of gabion wall was taken. Comparison was made based on the reading obtained. It was found that the gabion wall with 20% of palm oil clinker has 25% extra displacement when compared with conventional gabion. The result shows that palm oil clinker is less effective to use as alternative material for gravel in constructing of gabion wall. However, there are still have potential to reduce the usage natural resources.